2019
DOI: 10.22543/7674.62.p190195
|View full text |Cite
|
Sign up to set email alerts
|

Modern concepts in non-surgical esthetics; a review

Abstract: New non-surgical esthetics is the most dynamic field in contemporary medicine. At the same time, it is greatly influenced by our contemporary society. This paper reviews modern methods used in non-surgical esthetics, especially in Romania. From injectology and non-surgical face lifting to non-surgical body contouring, we analyzed all procedures performed by Romanian physicians, and we show the advantages and disadvantages of the advanced esthetic procedures. Injectology typically implies hyaluronic acid, botox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition, such considerations are applicable in the case of the disc at which the degenerative processes occurred (4,8,9). At present, it is certain that the resistance of the disc varies depending on the degree of degeneration, leading, in turn, to a decreased resistance in cases of moderate degeneration and increased rigidity, and subsequently to a decrease of the force absorption power, in case of severe degeneration (6,7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Furthermore, the parallelism between the load on the one hand, and the disc degeneration, on the other hand, can engage the fibrous annulus in a vicious cycle, which invariably results in irreversible ruptures (7).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, such considerations are applicable in the case of the disc at which the degenerative processes occurred (4,8,9). At present, it is certain that the resistance of the disc varies depending on the degree of degeneration, leading, in turn, to a decreased resistance in cases of moderate degeneration and increased rigidity, and subsequently to a decrease of the force absorption power, in case of severe degeneration (6,7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Furthermore, the parallelism between the load on the one hand, and the disc degeneration, on the other hand, can engage the fibrous annulus in a vicious cycle, which invariably results in irreversible ruptures (7).…”
Section: Resultsmentioning
confidence: 99%
“…Another possible explanation could be the degradation of the adhesion molecules and growth factors by the local proteinases (12)(13)(14). Moreover, the expression of different tissue proteases in burn wounds could influence the prognosis (15). As a confirmation, some authors have associated increased MMP-9 concentrations with delayed healing of burned skin (16).…”
Section: Role and Dynamics Of Matrix Metalloproteinase 9 And Tissue Inhibitor Of Metalloproteinase 1 In Burn Patientsmentioning
confidence: 97%
“…Minimally invasive cosmetology is the most dynamic field of contemporary medical cosmetology [ 9 ]. The data of ASAPS indicated that the injection means were used to fill or shape the face with other intermediate treatments such as hyaluronic acid (HA) and botox, accounting for 80.9% of less-invasive procedures at the end up to 2019 [ 10 ], following by laser treatment, radiofrequency ablation treatment, chemical peeling and other skin surface treatment tools.…”
Section: Introductionmentioning
confidence: 99%